Renewable Energy for Competitive Growth: Challenges and Opportunities - Muzho, Neda (Research Papers, 2024)
Renewable energy has emerged as a crucial solution to address the challenges posed by climate change and the increasing demand for energy. This paper aims to explore the challenges and opportunities associated with the adoption of renewable energy for achieving competitive growth. The study examines the current state of renewable energy technologies, identifies the barriers to their widespread implementation, and highlights the potential benefits and opportunities for economic growth. The findings suggest that while there are challenges to overcome, renewable energy presents significant opportunities for sustainable development and a competitive advantage in the global market. The literature review was supplemented by an additional review on the criteria used by different policymakers and case studies. The final presentation of the results creates a taxonomy landscape of criteria for the social and political perspectives as well as success story in terms of CSR. The strategical importance in this regard is related to the perspective in the decision-making by policy makers in different countries.